Sustainable consumption and production in the clothes industry to reduce the effect of climate change - Adellia, Niken; Ismail, Yunita (Journal of Waste and Sustainable Consumption, 2024)
Background: Climate change is undoubtly can not be resisted. The impacts of climate change are becoming more and more evident in front of our eyes, with increasing hydrological disasters. On the one hand, fashion is one of the largest contributors to carbon emissions in the world, especially after the fast fashion trend. Therefore, further study how to make fashion more sustainable should be done and implemented. By thus, in this journal want to answering the question what should the production side act to be more sustainable in produce textile & clothes regarding to reduce effect of climate change and from the consumers perspective side, how the consumers contribute regarding to reduce bad effect of fashion for climate. Methods: By using descriptive qualitative method in the form of collecting and compiling the results of the literature, analyzing the results of the literature, and interpreting the results of the literature based on topic relating to the title of the article. Findings: The result was some kind changing in the production side should be done such as, changing used electricity,used of dye, altered the material and made circular fashion industry, and for consumer there are some alternative thing that could be done such as buy ethical brand, buy second hand, and shopping less. Conclusion: By this reseach finding, so hopefully for further act should be done by collaboration between all key player toward fashion industry.